Determinants Of Ekonomic Growth In ASEAN-10 - Dinayati, Lilis; Rosnawintang, Rosnawintang; Balaka, Yani (Jurnal Ekonomi, 2024)
Stock price fluctuations in energy sector companies are often influenced by various factors, including the company's financial performance. One indicator that can affect stock price fluctuations is the profitability ratio, which includes the Return on Assets (ROA) and Earning Per Share (EPS) ratios. This study aims to analyze the effect of profitability ratios on stock prices of energy sector companies in Indonesia. The method used in this study is panel data regression, which allows analyzing the relationship between independent and dependent variables by taking into account variations between companies and over time. The results show that the Return on Assets (ROA) ratio has a positive effect on stock prices of energy sector companies, meaning that the higher the ROA, the higher the company's stock price. On the other hand, the Earning Per Share (EPS) ratio does not show a significant effect on stock prices in the energy sector. These findings contribute to the understanding of the factors that influence stock prices in the energy sector, as well as their implications for investors and company managers in making investment decisions and financial policies.